2013
DOI: 10.1016/j.krcp.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between periodontitis and chronic kidney disease in Korean adults

Abstract: BackgroundPeriodontitis and chronic kidney disease (CKD) are important health issues; however, the association between periodontitis and CKD markers, especially in Korean adults, remains elusive.MethodsData on 15,729 Korean adults were obtained from the Korean National Health and Nutritional Examination Surveys IV and V. The CKD markers included a decreased estimated glomerular filtration rate (eGFR;<60 mL/min/1.73 m2), proteinuria, and hematuria. Odds ratios (ORs) and 95% confidence intervals were measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 35 publications
1
35
1
Order By: Relevance
“…Figure shows the flowchart for the search and study selection process. A total of 17 studies was selected and included, of which nine studies reported periodontal disease as the exposure and CKD as the outcome . Alternately, eight reported the association of CKD as the exposure and periodontal disease as the outcome …”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the flowchart for the search and study selection process. A total of 17 studies was selected and included, of which nine studies reported periodontal disease as the exposure and CKD as the outcome . Alternately, eight reported the association of CKD as the exposure and periodontal disease as the outcome …”
Section: Resultsmentioning
confidence: 99%
“…Most of the included studies demonstrated an association between CKD and periodontitis, with ORs ranging from 1.39 (1.03–1.89) (Han et al., ) to 4.0 (2.7–5.9) (Sharma et al., ). When considering the type of study, all the cohort studies found an association between CKD and periodontitis (Grubbs et al., ), (Grubbs et al., ) (Iwasaki et al., ), whereas, some cross‐sectional (Messier et al., ) and case–control (Brotto et al., ) studies failed to find it.…”
Section: Resultsmentioning
confidence: 99%
“…Table describes the characteristics of 7 case‐control studies and 38 cross‐sectional studies on the non‐directional association, and lists them in reverse publication order . Among them, 24 had a statistical analysis, but 7 did not consider any confounding factors (Appendix A) .…”
Section: Resultsmentioning
confidence: 99%